2008
DOI: 10.1002/ptr.2376
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of osteoarthritis with Pycnogenol®. The SVOS (San Valentino osteo‐arthrosis study). evaluation of signs, symptoms, physical performance and vascular aspects

Abstract: The aim of this double-blind, placebo-controlled study was to evaluate the efficacy of 100 mg Pycnogenol daily (oral capsules) in a 3 month study in patients with osteoarthritis (OA). OA symptoms were evaluated by WOMAC scores, mobility by recording their walking performance (treadmill). Treatment (77 patients) and placebo group (79) were comparable for age, sex distribution, WOMAC scores, walking distances and use of antiinflammatory drugs. The global WOMAC score decreased by 56% (p < 0.05) in the treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 14 publications
2
63
0
Order By: Relevance
“…Downregulation of 5-lipoxygenase consequently decreases leukotriene levels in asthmatic patients (Canali et al, 2009), and the anti-inflammatory activity of PYC may be best used in combination with inhalation corticosteroids, enabling reduced dosage and frequency of inhalation corticosteroid administration and potentially reducing the need for other asthma medications . Anti-inflammatory properties include alleviating pain and stiffness in arthritis and osteoarthritis patients (Belcaro et al, 2008a), and PYC is a promising antiarthritic drug candidate.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Downregulation of 5-lipoxygenase consequently decreases leukotriene levels in asthmatic patients (Canali et al, 2009), and the anti-inflammatory activity of PYC may be best used in combination with inhalation corticosteroids, enabling reduced dosage and frequency of inhalation corticosteroid administration and potentially reducing the need for other asthma medications . Anti-inflammatory properties include alleviating pain and stiffness in arthritis and osteoarthritis patients (Belcaro et al, 2008a), and PYC is a promising antiarthritic drug candidate.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Eighteen studies were of confirmatory design (Altman 2001; Appelboom 2001; Belcaro 2008; Biegert 2004; Blotman 1997; Chopra 2004; Chopra 2013; Jung 2001; Jung 2004; Kuptniratsaikul 2009; Kuptniratsaikul 2011; Leblan 2000; Lequesne 2002; Maheu 1998; Maheu 2013; Pavelka 2010; Sengupta 2008; Sengupta 2010), that is effect size was estimated a priori, statistical power and alpha level were set, and sample size recruitment undertaken according to these calculations. The remaining 32 studies were of exploratory design and were generally of poorer methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 new studies, including four studies published between 1988 and 1997 that had been overlooked in the previous review (Bernhardt 1991; Huber 1991; Schadler 1988; Schmelz 1997), were identified for inclusion in the updated review (Adegbehingbe 2008; Altman 2001; Appelboom 2001; Badria 2002; Belcaro 2008; Biegert 2004; Biller 2002; Bliddal 2000; Cao 2005; Cheras 2010; Chopra 2004; Chopra 2011; Chopra 2013; Cisar 2008; Farid 2007; Frerick 2001; Gupta 2011; Jung 2001; Jung 2004; Kimmatkar 2003; Kuptniratsaikul 2009; Kuptniratsaikul 2011; Leblan 2000; Lequesne 2002;Maheu 2013;Majima 2012;Medhi 2009; Mehta 2007; Oben 2009; Pavelka 2010; Piscoya 2001; Rein 2004a; Schmid 2000; Sengupta 2008; Sengupta 2010; Sontakke 2007; Teekachunhatean 2004; Vishal 2011; Warholm 2003;Wigler 2003;Winther 2005). These new studies were added to the four studies of oral herbal products included in the original review (Blotman 1997; Ferraz 1991; Maheu 1998; Mills 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations